DEVELOPMENT OF A TURN-BASED MATHEMATICS EDUCATIONAL GAME FOR FOURTH-GRADE ELEMENTARY STUDENTS USING ADDIE MODEL - Rifqi, Muhammad; Irianto, Kurniawan Dwi; Mahardhika, Galang Prihadi (Department of Informatics Engineering, Faculty of Science and Technology, Universitas Islam Negeri Alauddin, Makassar, Indonesia, 2026)
Mathematics is often perceived as a difficult and abstract subject by elementary school students, which can lead to low learning interest and motivation. This condition is reflected in the 2022 Programme for International Student Assessment (PISA) results, which indicate relatively low mathematical proficiency among students in Indonesia. Previous studies have explored educational games for mathematics learning. However, limited research explicitly integrates strategic turn-based mechanics with graded mathematical difficulty levels to encourage reflective decision-making among elementary students. This study aims to develop an Android-based educational game entitled Petualangan Ksatria as a supplementary learning medium for fourth-grade elementary mathematics learning. The game development process followed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model and was implemented using the Unity game engine. Functional validation was conducted through black-box testing to ensure that all game modules and features operated in accordance with predefined specifications. Furthermore, the evaluation stage employed User Acceptance Testing (UAT), involving 31 students and one fourth-grade teacher. The results indicate a student acceptance score of 85%, classified as Very Satisfactory, and a teacher evaluation score of 80%, categorized as Satisfactory. These findings indicate that Petualangan Ksatria is aligned with the Kurikulum Merdeka in Indonesia and shows potential as an engaging supplementary learning medium for mathematics education in elementary schools.